Implementation of One Health approach in Tanzania: Strengths and challenges - Vianney, John-Mary; Kimaro, Esther G.; Buza, J.; Knight-Jones, Theodore J.D.; Fèvre, Eric M.; Richards, Shauna; Shirima, Gabriel M. (CAB International, 2024)
One Health (OH) approach has recently been defined by the OH High-Level Expert Panel (OHHLEP) as an integrated, unifying approach that aims to sustainably balance and optimize the health of people, animals, and ecosystems. Under the Prime Minister’s Office (PMO), the OH section (OHS) is responsible for OH implementation. The OHS task is to bring together multiple sectors and disciplines to work together with clear OH approach coordination in the country. Following the recent revision of the OH strategic plan (2022–2027), the OHS is now eligible to receive funding from the government. In addition, through OHS, Tanzania has supporting documents for OH, including the National Action Plan for Antimicrobial Resistance, the prioritized list of zoonotic diseases, and strategic prevention and control plans. Despite these developments in OH in Tanzania, the Capacitating One Health in Eastern and Southern Africa (COHESA) project helped identify the challenges and gaps that Tanzania faces in OH implementation. A baseline assessment study was conducted in four settings: Desktop Review, Focus Group Discussion (FGD), Key Informants Interview (KII), and OH net mapping. Results showed that the country’s OH challenges include a lack of OH resources, OH education inclusiveness, and OH awareness at the subnational level. There are limited suitable OH monitoring mechanisms to assess the progress of the OH approach in Tanzania. Thus, COHESA supports the country in addressing these challenges to improve at all levels of OH sectoral performance in the context of OH governance, education, and implementation.